Development of Work-Based Learning Models Based on Work Readiness (WBL-WoRe) - Bambang Sudarsono (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2022)
In recent years, graduates of Vocational High Schools (SMK) still dominate the unemployment rate in Indonesia. Unemployment which is the main problem can be overcome by increasing the work readiness of vocational students with support from industry. The aim of the research is to develop a work-ready-oriented work-based learning model (WBL-WoRe) that is feasible and effective to use to improve the work readiness of vocational students. This research design adopted the Richey and Klein research and development (R&D) design with the stages of model development, internal validation and external validation. The research subjects used were students of SMK Muhammadiyah 1 Salam concentration of automotive engineering expertise, totaling 137 students. The research object is the Ultratune, Astra Daihatsu Magelang and Toyota Nasmoco Magelang workshops. The technique of collecting work readiness data uses observation sheets of attitudes, knowledge and skills. Further analyzed by quantitative methods. This study shows that from the results of external validation (limited and expanded trials) the WBL-WoRe model is feasible and effective in increasing the work readiness of SMK students with a very good category. Keywords: Work-Based Learning, Learning Models, Work Readiness